Kalhana's rajatarangini : a chronicle of the Kings of Kasmir - Stein, M.A. (Delhi : Bangalore : Patna : Motilal Bonarsidass, 1988)
Kalhana s Rajatarangini is the most famous historical poem which records the oldest and fullest history of the legendary kings of Kashmir as well as gives accounts of the Kashmirian kings of the historical period. It consists of eight chapters and draws upon earlier sources, notably the Nilamata Purana. Sir Stein recognising the inestimable value of the only work of its kind, succeeded in publishing the critical edition of the text as early as in 1892. The interest of this treatise for Indian history generally lies in the fact that it represents a class of Sanskrit composition which comes nearest in character to the chronicles of Medieval Europe and of the Muhammadan East. Together with the later Kashmir chronicles which continue Kalhana s narrative, it is practically the sole extant specimen of this class. Its author s object is to offer a connected narrative of the various dynasties which ruled Kashmir from the earliest period down to his own time. The final portion of the work, considerable both in extent and historical interest, is devoted to the accounts of the events which the author knew by personal experience or from the relation of living witnesses. These events are narrated from the point of view of a more or less independent chronicler and by no means the purely panegyrical object of the court-poet.
Vol. III